ChemInform Abstract: Synthesis of Novel Pyrano[2, 3‐b]pyridines from α, α′‐Bis(substituted‐benzylidene)cycloalkanones. Issue 46 (24th October 2013) - Bigdeli, Mohammad Ali; Marjani, Katayon; Farokhi, Elinaz; Sheikhosseini, Enayatollah; Ghazanfari, Dadkhoda
Abstract The reactions are conducted under mild conditions.